Variability and the Size-Luminosity Relation of the Intermediate-mass AGN in NGC 4395 - Cho H; Woo JH; Hodges-Kluck E; Son D; Shin J; Gallo E; Bae HJ; Brink TG; Cho W; Filippenko AV; Horst JC; Ilic D; et al. (IOP PUBLISHING LTD, 2025)
We present a variability study of the lowest-luminosity Seyfert 1 nucleus of the galaxy NGC 4395 based on photometric monitoring campaigns in 2017 and 2018. Using 22 ground-based and space telescopes, we monitored NGC 4395 with a similar to 5-minute cadence during a period of 10 days and obtained light curves in the ultraviolet (UV), V, J, H, and K/K-s bands, as well as narrowband H alpha. The rms variability is similar to 0.13 mag in the Swift UVM2 and V filter light curves, decreasing down to similar to 0.01 mag in the K filter. After correcting for the continuum contribution to the H alpha narrow band, we measured the time lag of the H alpha emission line with respect to the V-band continuum as minutes in 2018, depending on assumptions about the continuum variability amplitude in the H alpha narrow band. We obtained no reliable measurements for the continuum-to-continuum lag between UV and V bands and among near-IR bands, owing to the large flux uncertainty of UV observations and the limited time baseline. We determined the active galactic nucleus (AGN) monochromatic luminosity at 5100 A, after subtracting the contribution of the nuclear star cluster. While the optical luminosity of NGC 4395 is two orders of magnitude lower than that of other reverberation-mapped AGNs, NGC 4395 follows the size-luminosity relation, albeit with an offset of 0.48 dex (>= 2.5 sigma) from the previous best-fit relation of Bentz et al.